2022
DOI: 10.3390/ijerph191710978
|View full text |Cite
|
Sign up to set email alerts
|

Peer Victimization and Adolescent Mobile Social Addiction: Mediation of Social Anxiety and Gender Differences

Abstract: Social media addiction has become one of the typical problem behaviors during adolescence. The present study examined the mediation of social anxiety between peer victimization and adolescent mobile social addiction and tested whether gender could moderate the direct and indirect effects of peer victimization. 649 adolescents between 12 and 19 years of age (Mage = 14.80, SDage = 1.82) completed the anonymous survey. The results found that social anxiety was a mediator linking peer victimization to mobile socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The PROCESS has been widely used in previous studies to reveal the mediating effects, moderating effects, and the combined complex effects of mediators and moderators ( 41 ). Age ( 42 ), gender ( 43 ), and daily use time ( 44 , 45 ) were included in the regression model to control their potential effects.…”
Section: Methodsmentioning
confidence: 99%
“…The PROCESS has been widely used in previous studies to reveal the mediating effects, moderating effects, and the combined complex effects of mediators and moderators ( 41 ). Age ( 42 ), gender ( 43 ), and daily use time ( 44 , 45 ) were included in the regression model to control their potential effects.…”
Section: Methodsmentioning
confidence: 99%
“…Relational victimization is a common stressful social experience for college students [ 76 ], especially for females. It would induce serious psychological distress and further lead to adverse adaptation outcomes, such as mobile social addiction, video game addiction, and other problematic behaviors [ 24 , 55 ]. For female college students, the negative effects of relational victimization are even more pronounced [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that parasocial relationships support social function [ 53 ] and can be resources to substitute or compensate for close relationships and social belonging [ 46 , 54 ]. In addition, existing studies also indicated that peer victimization is a predictor of mobile social addiction [ 55 , 56 ], which means that people whose social life is hindered may find some controllable ways to compensate. As discussed above, relational victimization is a common adversity for female college students who will face the situation of lacking social contacts [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…These digital spaces offer a sense of belonging, where individuals can share their experiences, fears, and triumphs without fear of judgment. The study by Tu et al [9] examined the positive aspects of social media in promoting mental health awareness and providing online support communities also Vannucci and Ohannessian [10] demonstrated that online peer support can significantly reduce symptoms of depression in adolescents, providing them with a valuable avenue for seeking advice and validation. Moreover, the anonymity offered by these communities can create a safe space for adolescents who may feel hesitant to open up in traditional face-to-face settings.…”
Section: Positive Aspects: Mental Health Awareness and Online Supportmentioning
confidence: 99%